Self-expanding water shutoff material for tunnel and preparation method of self-expanding water shutoff material
Through the combination of nanocomposite modified polyurethane, epoxy acrylate and highly absorbent resin, the shortcomings of traditional water blocking materials in terms of expansion rate, water resistance, bonding strength and curing time are solved, and the efficient and stable sealing effect of tunnel water blocking materials is achieved.
Patent Information
- Application Number
- CN202510870660.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-09-02
AI Technical Summary
Traditional water blocking materials have insufficient expansion rate, poor water resistance, low bonding strength to surrounding rock and long curing time, so they cannot efficiently fill complex cracks in tunnels and seal them stably for a long time.
By nanocomposite and crosslinking modification of polyurethane and epoxy acrylate, a highly absorbent resin is introduced, and a filler and additives are combined to form a self-expanding water-blocking material with high expansion rate and strong water resistance.
It has achieved efficient filling of complex cracks in the tunnel, long-term stable sealing, excellent water resistance, significant improvement in bonding strength, rapid curing, and adapting to the water blocking needs of complex tunnel environments.
Smart Images

Figure BDA0005469788150000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a self-expanding water-blocking material for tunnels and a preparation method thereof. Background Art
[0002] As a vital component of transportation infrastructure, tunnel construction and operational safety often face challenges in complex geological environments. Water inrush and flooding are among the most common and devastating issues. These hazards not only directly threaten the lives of construction workers and delay construction schedules, but can also cause long-term damage to the tunnel lining, leading to recurring leakage during later operations and severely impacting the tunnel's service life and reliability. Traditional water-blocking materials have exposed significant limitations when dealing with such problems: First, the expansion performance is insufficient. The volume expansion rate of conventional materials is mostly within 2 times, which makes it difficult to effectively fill the complex cracks with a width of 0.1-5mm in the tunnel surrounding rock, especially under high permeability geological conditions such as water-rich fault zones, and cannot form a continuous sealing barrier; second, the water resistance is poor. The material is prone to swelling and degradation after long-term immersion in the groundwater environment, resulting in attenuation of expansion performance or even failure, causing secondary leakage; third, the bonding strength with the surrounding rock is low. The bonding strength of most materials with common surrounding rocks such as granite and limestone is less than 1.0MP, and they are prone to peeling and falling off due to water pressure or deformation of the surrounding rock, which weakens the water-blocking effect; fourth, the curing time is long. Traditional cement-based materials require several hours or even longer to initially cure, which cannot meet the rapid water-stopping needs in emergency situations such as tunnel water inrush.
[0003] To address these issues, the industry has attempted to optimize by adjusting material ratios or introducing simple modification technologies, but the results have been limited. For example, while conventional polyurethane materials have a certain degree of expansion, their molecular chains have weak polarity and insufficient bonding with the surrounding rock. Epoxy resins, while having good adhesion, are brittle after curing and have difficulty adapting to surrounding rock deformation. Cement-based materials, however, are limited by their inherent rigidity and cannot maintain sealing properties under complex stress environments. Therefore, developing a water-blocking material that combines a high expansion rate, excellent water resistance, strong bonding, and rapid curing properties has become an urgent need in the field of disaster prevention and mitigation in tunnel engineering.
[0004] Based on this background, the present invention proposes a self-expanding water-blocking material for tunnels and its preparation method. By nanocompositing and crosslinking polyurethane and epoxy acrylate, the material's hydrophilicity, crosslinking density, and interfacial bonding properties are enhanced. A highly absorbent resin is introduced as an auxiliary expansion source. Combined with the synergistic effects of fillers and additives, the resulting material is a novel water-blocking material that can adapt to the complex environments of tunnels, efficiently fill cracks, and provide long-term, stable sealing. This provides key technical support for preventing and controlling water inrush hazards in tunnels. Summary of the Invention
[0005] The purpose of the present invention is to provide a self-expanding water-blocking material for tunnels and a preparation method, which solves the problems of traditional water-blocking materials such as insufficient expansion rate, poor water resistance, low bonding strength with surrounding rocks and long curing time, and inability to efficiently fill complex cracks in tunnels and provide long-term stable sealing.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A self-expanding water plugging material, the raw materials of which include, by mass percentage:
[0008] Modified polyurethane: 30-40%;
[0009] Modified epoxy acrylate: 25-35%;
[0010] Super absorbent resin: 10-15%;
[0011] Filler: 15-20%;
[0012] Dibutyl phthalate: 1-3%;
[0013] Ammonium persulfate: 0.5-2%;
[0014] N,N'-methylenebisacrylamide: 0.5-1%;
[0015] Silicone defoamer: 1.5-4%;
[0016] Deionized water: balance;
[0017] The preparation method of the modified polyurethane comprises the following steps: A1, firstly, dehydrating the polyether diol under vacuum at 110-115°C, cooling the polyether diol to 60-62°C, adding diisocyanate, and heating the polyol to 80-82°C for reaction; then, cooling the polyol to 39-41°C, adding a mixed solution of a carboxyl chain extender and acetone, stirring the mixture, and heating the mixture to 60-63°C for reaction; A2, dispersing nano-SiO2 in anhydrous ethanol and ultrasonically treating the mixture, adding a silane coupling agent and continuing ultrasonication to obtain a dispersion, and dropwise adding the dispersion into the prepolymer for reaction; cooling the polyol to 30-33°C, adding triethylamine, stirring the mixture to form a stable emulsion, and performing reduced pressure distillation.
[0018] According to a preferred embodiment of the present invention, polyether diol: purchased from Wanhua Chemical Group Co., Ltd., model 2000 (molecular weight 2000, hydroxyl value 56 mgKOH / g); or purchased from Hongbaoli Group Co., Ltd., model HP-2000 (molecular weight 2000, hydroxyl value 56±2 mgKOH / g).
[0019] According to a preferred embodiment of the present invention, diisocyanate: purchased from Wanhua Chemical Group Co., Ltd., model number is TDI-80 (toluene diisocyanate, purity ≥99.5%).
[0020] According to a preferred embodiment of the present invention, the carboxyl chain extender is purchased from Aladdin Reagent (Shanghai) Co., Ltd., model D100203 (dimethylolpropionic acid, DMPA, purity ≥99%); or purchased from MacLean Biochemical Technology Co., Ltd., model DMPA-01 (purity ≥99%).
[0021] According to a preferred embodiment of the present invention, acetone is purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd. and is industrial grade acetone (purity ≥ 99.5%).
[0022] According to a preferred embodiment of the present invention, nano-SiO2: purchased from Nano Micro Technology Co., Ltd., model number is NanoSiO2-50 (particle size 50±10nm, specific surface area ≥300m 2 / g); or purchased from Xiamen Tungsten Co., Ltd., model WSiO2-80 (particle size 80±15nm, specific surface area ≥250m 2 / g).
[0023] According to a preferred embodiment of the present invention, anhydrous ethanol is purchased from COFCO Biotechnology Co., Ltd. and is of the type anhydrous ethanol (purity ≥ 99.5%).
[0024] According to a preferred embodiment of the present invention, the silane coupling agent is purchased from Nanjing Shuguang Chemical Group Co., Ltd., model KH-550 (γ-aminopropyltriethoxysilane, purity ≥98%); or purchased from Hubei Xingfa Chemical Group Co., Ltd., model XH-550 (purity ≥98%).
[0025] According to a preferred embodiment of the present invention, super absorbent resin (SAP): purchased from Satellite Chemical Co., Ltd., model number is SAP-200 (water absorption rate ≥ 300g / g, particle size 100-200 mesh); or purchased from Wanhua Chemical Group Co., Ltd., model number is SAP-300 (water absorption rate ≥350g / g, particle size 80-150 mesh).
[0026] According to a preferred embodiment of the present invention, filler (calcium carbonate / silicon powder): calcium carbonate was purchased from Guangxi Calcite Mining Co., Ltd., and the model was 500 mesh heavy calcium carbonate (whiteness ≥90%, CaCO3 content ≥98%); silicon powder was purchased from Jiangsu Donghai Silica Powder Co., Ltd., and the model was 1000 mesh fused silicon powder (SiO2 content ≥99.9%, particle size distribution 1000±200 mesh).
[0027] According to a preferred embodiment of the present invention, dibutyl phthalate (DBP) is purchased from Jinling Petrochemical Co., Ltd., model DBP-01 (purity ≥99.5%, acid value ≤0.1 mgKOH / g).
[0028] According to a preferred embodiment of the present invention, ammonium persulfate (APS) is purchased from Hebei Jiheng Pharmaceutical Co., Ltd., model APS-01 (purity ≥98%, effective oxygen content ≥5.5%); or purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model D100205 (purity ≥98%, active oxygen content ≥6.5%).
[0029] According to a preferred embodiment of the present invention, N,N'-methylenebisacrylamide (MBA): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model MBA-01 (purity ≥98%, molecular weight ≤1000); or purchased from Aladdin Reagent (Shanghai) Co., Ltd., model D100207 (purity ≥98%).
[0030] According to a preferred embodiment of the present invention, the organosilicon defoamer is purchased from Dow Corning (China) Investment Co., Ltd., model DC-654 (organosilicon defoamer, active content ≥95%); or purchased from Jiangsu Chenguang New Materials Co., Ltd., model CM-01 (organosilicon defoamer, defoaming efficiency ≥90%).
[0031] According to a preferred embodiment of the present invention, deionized water is purchased from Midea Group Pure Water Equipment Co., Ltd. and is industrial-grade deionized water (conductivity ≤ 10 μS / cm, total dissolved solids ≤ 10 mg / L).
[0032] In the preparation of the modified polyurethane of the present invention, after the polyether diol is dehydrated by vacuum dehydration to remove moisture, it undergoes a condensation reaction with diisocyanate at 80-82°C to form an isocyanate-terminated (-NCO) prepolymer; then, a mixed solution of a carboxyl chain extender (such as dimethylol propionic acid) and acetone is added, and the -NCO reacts with the carboxyl group (-COOH) at 60-63°C to form an amide bond (-CONH-), while simultaneously introducing a hydrophilic carboxyl group to impart water-swelling properties to the polyurethane; after the nano-SiO2 is ultrasonically dispersed in anhydrous ethanol, the surface hydroxyl groups react with the silane coupling agent (such as KH-550) to form a silane bond (-Si-OH) by hydrolysis. -, adsorbed on the SiO2 surface through electrostatic action to form silane-modified nanoparticles; when the dispersion is added dropwise to the prepolymer, the other end of the silane (such as the amino group) reacts with the -NCO or -OH of the polyurethane segment to graft the nano-SiO2 onto the polyurethane molecular chain to form a nano-enhanced structure of "polyurethane segment-silane-SiO2"; after cooling, triethylamine is added to neutralize the carboxyl group to form a stable carboxylate anion, so that the polyurethane is dispersed in water to form an emulsion, and after vacuum distillation to remove acetone, an aqueous polyurethane dispersion is obtained, whose hydrophilic segment provides the basis for subsequent water absorption and expansion.
[0033] According to a preferred embodiment of the present invention, in step A1, the vacuum dehydration time is 2-3 hours; the reaction time of heating to 80-82°C is 2-4 hours; the stirring time is 15-20 minutes; and the reaction time of heating to 60-63°C is 2-4 hours.
[0034] According to a preferred embodiment of the present invention, in step A2, the ultrasonic treatment time is 30-40 min; the ultrasonic treatment time is continued for 10-20 min, the dispersion is added dropwise to the prepolymer at a rate of 5-6 mL / min, the temperature in the prepolymer is 60-62 ° C, and the reaction time is 1-2 h; the stirring speed is 800-850 rpm, and the stirring time is 10-15 min.
[0035] According to a preferred embodiment of the present invention, the preparation method of the modified epoxy acrylate comprises: first, mixing epoxy resin and methyl methacrylate, heating to 80-82°C and adding a mixed solution of silane coupling agent and anhydrous ethanol and stirring, adding benzoyl peroxide to initiate polymerization, and heating to 90-92°C for reaction; B2, subsequently dispersing nano-montmorillonite in deionized water, adding hexadecyltrimethylammonium bromide and ultrasonically dispersing to form an intercalated nano-montmorillonite dispersion, adding the intercalated nano-montmorillonite dispersion to the above-mentioned prepolymer and continuing the reaction; cooling to 60-62°C, adding acrylic acid and a polymerization inhibitor hydroquinone and stirring, heating to 70-72°C for reaction, and reducing the pressure.
[0036] In the preparation of the modified epoxy acrylate of the present invention, after epoxy resin (E-51) and methyl methacrylate (MMA) are mixed, a silane coupling agent (such as KH-570) is added and stirred with anhydrous ethanol, the epoxy groups of the silane react with the hydroxyl groups of the epoxy resin, and at the same time, the silicon oxygen bond and the double bond of the MMA undergo free radical copolymerization to form an epoxy-acrylate semi-interpenetrating network (IPN) prepolymer; nano-montmorillonite (MMT) is intercalated and ultrasonically dispersed with hexadecyltrimethylammonium bromide (CTAB), and the interlayer distance increases to form a "CTAB-montmorillonite" intercalation structure; when the nano-montmorillonite is added to the prepolymer, the epoxy groups or acrylate groups react with the silicon oxygen bonds of the montmorillonite. The bonds are combined through coordination or hydrogen bonding, while the double bonds of MMA and epoxy groups undergo free radical copolymerization under the initiation of benzoyl peroxide (BPO), so that the montmorillonite sheets are embedded in the polymer network to form a nano-composite structure of "polymer chain-montmorillonite sheets". Subsequently, acrylic acid (AA) and the inhibitor hydroquinone are added, and the double bonds of AA continue to copolymerize with the remaining epoxy groups or methacrylate groups, further cross-linking to form a three-dimensional network. At the same time, carboxyl groups (-COOH) are introduced to enhance hydrophilicity. After reducing pressure to remove unreacted MMA, a modified epoxy acrylate prepolymer with a high cross-linking density is obtained. Its interpenetrating network structure provides the material with high modulus and water resistance.
[0037] According to a preferred embodiment of the present invention, the epoxy resin is purchased from Wanhua Chemical Group Co., Ltd., model E-51 (epoxy equivalent 184-190 g / eq, purity ≥99.5%); or purchased from Baling Petrochemical Co., Ltd., model CYD-128 (epoxy equivalent 190-200 g / eq, purity ≥99%).
[0038] According to a preferred embodiment of the present invention, the methyl methacrylate is purchased from Wanhua Chemical Group Co., Ltd., model MMA-01 (purity ≥99.5%, acid value ≤0.1 mgKOH / g); or purchased from Jilin Petrochemical Co., Ltd., model JLM-01 (purity ≥99.5%, volatile matter ≤0.1%).
[0039] According to a preferred embodiment of the present invention, the benzoyl peroxide is purchased from Aladdin Reagent (Shanghai) Co., Ltd., model D100205 (purity ≥98%, active oxygen content ≥6.5%); or purchased from MacLean Biochemical Technology Co., Ltd., model BPO-01 (purity ≥98%, particle size ≤50 μm).
[0040] According to a preferred embodiment of the present invention, the nano-montmorillonite was purchased from Nano Micro Technology Co., Ltd., and the model is NanoMMT-50 (particle size 50±10nm, specific surface area ≥300m 2 / g, cation exchange capacity ≥70meq / 100g); or purchased from Zhejiang Fenghong New Materials Co., Ltd., model Fenghong-MMt-80 (particle size 80±15nm, specific surface area ≥250m 2 / g, cation exchange capacity ≥65meq / 100g).
[0041] According to a preferred embodiment of the present invention, the hexadecyltrimethylammonium bromide is purchased from Aladdin Reagent (Shanghai) Co., Ltd., model D100207 (purity ≥98%, bromine content ≥96%); or purchased from Sinopharm Chemical Reagent Co., Ltd., model CTAB-01 (purity ≥98%, bromine content ≥95%).
[0042] According to a preferred embodiment of the present invention, the acrylic acid is purchased from Wanhua Chemical Group Co., Ltd., model AA-01 (purity ≥99.5%, inhibitor content ≤0.01%); or purchased from Satellite Chemical Co., Ltd., model SAP-AA-01 (purity ≥99.5%, inhibitor content ≤0.01%).
[0043] According to a preferred embodiment of the present invention, the polymerization inhibitor hydroquinone is purchased from Aladdin Reagent (Shanghai) Co., Ltd., model D100209 (purity ≥99%, melting point ≥170°C); or purchased from Jinling Petrochemical Co., Ltd., model HQ-01 (purity ≥99%, melting point ≥168°C).
[0044] According to a preferred embodiment of the present invention, in step B1, the stirring time of the mixed solution is 10-20 minutes, and the reaction time after heating to 90-90° C. is 2-3 hours.
[0045] According to a preferred embodiment of the present invention, in step B2, the ultrasonic dispersion time is 2-3 hours; the dropwise acceleration rate of the nano-montmorillonite dispersion added to the above-mentioned prepolymer is 3-4 mL / min, the temperature in the prepolymer is 80-82°C, and the reaction time is continued for 1-2 hours; the stirring time is 10-20 minutes, and the temperature is raised to 70-72°C and the reaction time is 1.5-2 hours.
[0046] The present invention also provides a method for preparing the self-expanding water-blocking material, comprising the following steps:
[0047] S1. After weighing each raw material according to the formula ratio, add modified polyurethane and modified epoxy acrylate premix in a high-speed mixer in sequence; then add super absorbent resin, calcium carbonate, silica powder, dibutyl phthalate, and N,N'-methylenebisacrylamide in sequence and stir;
[0048] S2. Then, ammonium persulfate and an organosilicon defoamer are added and stirred to obtain a mixed slurry. Finally, the mixed slurry is injected into a mold, placed in a constant temperature box at 40-42° C. for curing, and then heated to 60-65° C. for curing.
[0049] During the preparation process of the final material of the present invention, the hydrophilic chain segment (-COOH) of the modified polyurethane and the super absorbent resin (SAP) rapidly absorb water and swell in water, providing initial expansion power; the highly cross-linked network of the modified epoxy acrylate limits the expansion rate, avoiding material rupture or sudden surge caused by rapid expansion; nano-SiO2 and montmorillonite flakes disperse stress through interface bonding (such as hydrogen bonds and van der Waals forces), thereby improving the crack resistance of the material; fillers (calcium carbonate, silicon micropowder) serve as rigid support to enhance the mechanical strength of the material; dibutyl phthalate (DBP) plasticizes the polyurethane chain segment to improve the flexibility of the material; ammonium persulfate (APS) serves as an initiator to initiate free radical polymerization of acrylate or epoxy groups during the curing stage, thereby promoting cross-linking reaction; N,N'-methylenebisacrylamide (MBA) serves as a cross-linking agent to further cross-link with unreacted double bonds, thereby increasing network density; an organosilicon defoamer eliminates bubbles during the mixing process, thereby avoiding pores that reduce the density of the material; and deionized water adjusts the viscosity of the system to facilitate uniform filling of cracks during construction. Through the synergistic effect of "hydrophilic expansion-cross-linking restriction-nano-enhancement-interfacial bonding", the multiple components ultimately achieve the material's high expansion rate, water resistance, strong adhesion and controllable curing properties.
[0050] According to a preferred embodiment of the present invention, in step S1, the premixing speed is 300-400 rpm, and the premixing time is 5-10 min; the stirring speed is 800-1000 rpm, and the stirring time is 15-20 min.
[0051] According to a preferred embodiment of the present invention, in step S2, the stirring time is 5-10 minutes; the curing time in a 40-42°C constant temperature box is 2-4 hours, and the curing time at 60-65°C is 4-6 hours.
[0052] The present invention also provides an application of the self-expanding water-blocking material or the self-expanding water-blocking material prepared by the preparation method in a tunnel.
[0053] The beneficial effects of the present invention are:
[0054] The self-expanding water-blocking material of the present invention, through the collaborative design of dual-modified polymers and composite process optimization, has demonstrated significant technical advantages in tunnel engineering water blocking scenarios. Its core effects can be specifically explained from the following three aspects:
[0055] First, the material possesses outstanding high expansion and filling capabilities. Modified polyurethane and modified epoxy acrylate serve as core components, forming a dual-gain structure through nanoparticle grafting and interpenetrating network crosslinking. The hydrophilic segments of the modified polyurethane and the nanoparticles disperse stress, synergizing with the high crosslink density of the modified epoxy acrylate network to enable the material to rapidly absorb and expand upon contact with water. Combined with the auxiliary expansion source of superabsorbent resin, this further increases the volume expansion multiple. This multiple expansion mechanism enables it to effectively fill complex cracks of varying widths in tunnel surrounding rock, achieving continuous sealing from tiny gaps to wider cracks. This avoids the filling blind spots caused by insufficient expansion of traditional materials and provides efficient filling support for tunnel water inrush prevention.
[0056] Secondly, the material has excellent water resistance and long-term stability. Nano-silica and nano-montmorillonite are uniformly dispersed in the polymer network through ultrasonic dispersion and intercalation modification, respectively, forming a dual barrier of physical barrier and chemical stability. On the one hand, the dispersion effect of the nanoparticles slows the water penetration rate; on the other hand, the cross-linked network formed by the double-modified structure limits the swelling movement of the polymer chain segments. Even if it is exposed to groundwater for a long time, the material can still maintain stable expansion properties, effectively avoiding the secondary leakage problem caused by swelling and degradation of traditional materials. This water-resistant property enables the material to maintain a long-term sealing effect in highly permeable geological conditions such as water-rich fault zones, significantly improving the durability of the water blocking structure.
[0057] Third, the bonding strength between the material and the surrounding rock is significantly improved, and the interface bonding is strong. The silane coupling agent introduced during the preparation process acts as a "bridging agent" to form a chemical bond between the surface of the material and the active components of the surrounding rock. At the same time, the dispersed stress effect of the nanoparticles further enhances the interfacial bonding force. This strong bonding property enables the material to be firmly attached to the surface of the surrounding rock, and is not easily peeled off due to water pressure or deformation of the surrounding rock, greatly improving the long-term stability of the water blocking structure. In addition, the material's high compressive strength and crack resistance enable it to withstand the complex stress of the tunnel surrounding rock, avoiding cracking and failure due to deformation, and providing reliable bonding protection for scenarios such as tunnel lining crack repair.
[0058] In summary, the self-expanding water-blocking material of the present invention comprehensively solves the defects of traditional water-blocking materials in expansion performance, water resistance, bonding strength and curing efficiency through dual modification synergy and composite process innovation, and provides an efficient and reliable solution for engineering scenarios such as tunnel water inrush sealing, lining crack repair and advance grouting of water-rich fault zones. DETAILED DESCRIPTION
[0059] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content.
[0060] 1. Implementation
[0061] Example 1
[0062] Raw material composition: modified polyurethane 35g, modified epoxy acrylate 30g, super absorbent resin 12g, filler (calcium carbonate 10g, silicon powder 8g) 18g, dibutyl phthalate 2g, ammonium persulfate 1g, N,N'-methylenebisacrylamide 0.8g, silicone defoamer 3g, deionized water 1.2g.
[0063] Preparation method: Preparation of modified polyurethane: Take 100g of polyether diol with a molecular weight of 2000, vacuum dehydrate at 110℃ for 2.5h, cool to 61℃, add 45g of toluene diisocyanate (TDI-80), heat to 81℃ and react for 3h (to generate terminal isocyanate prepolymer with -NCO content of 5.3%); cool to 40℃, add a mixed solution of 6g of dimethylol propionic acid (DMPA) and 15g of acetone, stir for 18min, then heat to 62℃ and react for 3h (-NCO and carboxyl groups are completely separated). reaction); 5 g of nano-SiO2 (particle size 50 nm) was dispersed in 50 g of anhydrous ethanol and uniformly dispersed by ultrasonic treatment for 35 min; 0.5 g of γ-aminopropyltriethoxysilane (KH-550) was added and ultrasonic treatment was continued for 15 min; the dispersion was added dropwise to the prepolymer (61°C) at a rate of 5.5 mL / min and reacted for 1.5 h; after cooling to 32°C, 6.2 g of triethylamine was added, and the mixture was stirred at a speed of 820 rpm for 12 min. The acetone was removed by distillation under reduced pressure to obtain a modified polyurethane dispersion.
[0064] Preparation of modified epoxy acrylate: 100 g of epoxy resin (E-51) and 30 g of methyl methacrylate (MMA) were mixed and heated to 81°C. A mixed solution of 2 g of silane coupling agent (KH-550) and 10 g of anhydrous ethanol was added and stirred for 15 min. 0.5 g of benzoyl peroxide (BPO) was added to initiate polymerization and the temperature was raised to 91°C for 2.5 h to generate epoxy-acrylate semi-IPN prepolymer. Nano-montmorillonite 5 was added and the mixture was stirred for 15 min. g was dispersed in 50 g of deionized water, and 0.3 g of cetyltrimethylammonium bromide (CTAB) was added and ultrasonically dispersed for 2.5 h (to form an intercalated dispersion); the dispersion was added dropwise to the prepolymer (81°C) at a rate of 3.5 mL / min and reacted for 1.5 h; after cooling to 61°C, 10 g of acrylic acid and 0.1 g of hydroquinone as a polymerization inhibitor were added, stirred for 15 min, and the temperature was raised to 71°C to react for 1.75 h, and unreacted methyl methacrylate was removed under reduced pressure.
[0065] Mixing and curing: According to the above raw material composition formula, modified polyurethane and modified epoxy acrylate are weighed and pre-mixed at a speed of 320 rpm for 8 minutes; then, super absorbent resin, calcium carbonate, silica powder, dibutyl phthalate, and N,N'-methylenebisacrylamide are added in sequence and stirred at a speed of 880 rpm for 18 minutes; ammonium persulfate and silicone defoaming agent are added and stirred for 8 minutes; the mixed slurry is injected into the mold and placed in a constant temperature box at 41°C for curing for 3 hours, and then the temperature is raised to 62°C for curing for 5 hours.
[0066] Example 2
[0067] Raw material composition: modified polyurethane 38g, modified epoxy acrylate 32g, super absorbent resin 13g, filler (calcium carbonate 9g, silicon micropowder 8g) 17g, dibutyl phthalate 2.5g, ammonium persulfate 1.5g, N,N'-methylenebisacrylamide 0.7g, silicone defoamer 3.5g, deionized water 0.8g.
[0068] Preparation method: Preparation of modified polyurethane: take 100g of polyether diol with a molecular weight of 2000, vacuum dehydrate at 110℃ for 2h, cool to 60℃, add 45g of toluene diisocyanate (TDI-80), heat to 80℃ and react for 2h; cool to 39℃, add 6g of dihydroxymethylpropionic acid (DMPA) and 15g of acetone, stir for 15min, then heat to 60℃ and react for 2h; disperse 5g of nano-SiO2 (particle size 50nm) in 50g of anhydrous ethanol and ultrasonically treat for 30min; add 0.5g of silane coupling agent (KH-550) and ultrasonicate for 10min; add the dispersion dropwise to the prepolymer (60℃) at 5mL / min and react for 1h; cool to 30℃, add 6g of triethylamine, stir at 840rpm for 10min, and distill under reduced pressure. Preparation of modified epoxy acrylate: 100 g of epoxy resin and 30 g of methyl methacrylate were mixed, heated to 80°C, 2 g of silane coupling agent (KH-570) and 10 g of anhydrous ethanol were added, and stirred for 10 min; 0.5 g of benzoyl peroxide (BPO) was added, and the temperature was raised to 90°C for reaction for 2 h; 5 g of nano-montmorillonite was dispersed in 50 g of deionized water, and 0.3 g of hexadecyltrimethylammonium bromide was added and ultrasonically dispersed for 2 h; the dispersion was added dropwise to the prepolymer (80°C) at 3 mL / min and reacted for 1 h; after cooling to 60°C, 10 g of acrylic acid and 0.1 g of hydroquinone were added, stirred for 10 min, the temperature was raised to 70°C for reaction for 1.5 h, and the pressure was reduced. Mixing and curing: Weigh the modified polyurethane and modified epoxy acrylate according to the formula ratio and premix them (speed 380 rpm, time 10 min); then add super absorbent resin, calcium carbonate, silica powder, dibutyl phthalate, and N,N'-methylenebisacrylamide in sequence and stir (speed 920 rpm, time 20 min); add ammonium persulfate and silicone defoamer and stir for 10 minutes; inject the mixed slurry into the mold, place it in a constant temperature box at 42°C for curing for 4 hours, and then heat it to 65°C for curing for 6 hours.
[0069] Example 3
[0070] Raw material composition: modified polyurethane 32g, modified epoxy acrylate 34g, super absorbent resin 14g, filler (calcium carbonate 11g, silicon micropowder 8g) 19g, dibutyl phthalate 1.5g, ammonium persulfate 0.8g, N,N'-methylenebisacrylamide 0.6g, silicone defoamer 2.5g, deionized water 1.6g. Preparation method: Preparation of modified polyurethane: take 100g of polyether diol with a molecular weight of 2000, vacuum dehydrate at 110℃ for 3h (moisture 0.05%), cool to 62℃, add 45g of toluene diisocyanate (TDI-80), heat to 82℃ and react for 4h; cool to 41℃, add 6g of dimethylol propionic acid (DMPA) and 15g of acetone, stir for 20min, then heat to 63℃ and react for 4h; disperse 5g of nano-SiO2 (particle size 50nm) in 50g of anhydrous ethanol and ultrasonically treat for 40min; add 0.5g of silane coupling agent (KH-550) and ultrasonicate for 20min; add the dispersion dropwise to the prepolymer (62℃) at 6mL / min and react for 2h; cool to 33℃, add 6.2g of triethylamine, stir for 15min (speed 860rpm), and distill under reduced pressure. Preparation of modified epoxy acrylate: 100 g of epoxy resin was mixed with 30 g of methyl methacrylate, heated to 82°C, 2 g of silane coupling agent (KH-570) and 10 g of anhydrous ethanol were added, and stirred for 20 min; 0.5 g of benzoyl peroxide (BPO) was added, and the temperature was raised to 92°C for reaction for 3 h; 5 g of nano-montmorillonite was dispersed in 50 g of deionized water, and 0.3 g of hexadecyltrimethylammonium bromide was added and ultrasonically dispersed for 3 h; the dispersion was added dropwise to the prepolymer (82°C) at 4 mL / min and reacted for 2 h; after cooling to 62°C, 10 g of acrylic acid and 0.1 g of hydroquinone were added, stirred for 20 min, the temperature was raised to 72°C for reaction for 2 h, and the pressure was reduced. Mixing and curing: Weigh the modified polyurethane and modified epoxy acrylate according to the formula ratio and premix them (speed 420 rpm, time 12 min); then add super absorbent resin, calcium carbonate, silica powder, dibutyl phthalate, and N,N'-methylenebisacrylamide in sequence and stir (speed 1000 rpm, time 22 min); add ammonium persulfate and silicone defoamer and stir for 12 min; inject the mixed slurry into the mold, place it in a constant temperature box at 40°C for curing for 2 h, and then heat it to 63°C for curing for 4 h.
[0071] Comparative Example 1
[0072] Raw materials: 35g modified polyurethane (free of nano-SiO2), 30g modified epoxy acrylate, 12g superabsorbent resin, 18g filler (10g calcium carbonate, 8g silica powder), 2g dibutyl phthalate, 1g ammonium persulfate, 0.8g N,N'-methylenebisacrylamide, 3g organosilicon defoamer, and 1.2g deionized water. Preparation method: In the preparation of the modified polyurethane, only step A1 (dehydration of the polyether diol, reaction of the diisocyanate, and reaction of the carboxyl chain extender with acetone) is completed, and step A2 (nano-SiO2 dispersion, silane modification, and dropwise addition reaction) is omitted. The remaining steps are the same as in Example 1.
[0073] Comparative Example 2
[0074] Raw materials: 35g modified polyurethane, 30g modified epoxy acrylate (without nano-montmorillonite), 12g superabsorbent resin, 18g filler (10g calcium carbonate, 8g silica powder), 2g dibutyl phthalate, 1g ammonium persulfate, 0.8g N,N'-methylenebisacrylamide, 3g organosilicon defoamer, 1.2g deionized water. Preparation method: In the preparation of the modified epoxy acrylate, only step B1 (mixing the epoxy resin and methyl methacrylate, stirring the silane coupling agent with anhydrous ethanol, and initiating polymerization with benzoyl peroxide) is completed, and step B2 (nano-montmorillonite dispersion, intercalation treatment, and dropwise addition reaction) is omitted. The remaining steps are the same as in Example 1.
[0075] Comparative Example 3
[0076] Raw material composition (total mass 100g): modified polyurethane 38g, modified epoxy acrylate 35g, super absorbent resin 15g, filler (calcium carbonate 10g, silica powder 8g) 18g, dibutyl phthalate 3g, ammonium persulfate 2g, N,N'-methylenebisacrylamide 1g, silicone defoamer 4g, deionized water 0g (balance adjusted). Preparation method: Increase the amount of modified polyurethane and epoxy acrylate according to the formula ratio and reduce the filler to 18g; increase the stirring speed to 950rpm during the mixing and curing steps, shorten the curing time at 40°C to 2.5h, and shorten the curing time at 65°C to 4.5h. The remaining steps are the same as in Example 1.
[0077] 2. Performance Testing
[0078] The materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance according to the following method:
[0079] 1. The volume expansion rate test is based on GB / T 17671-1999 "Test method for strength of cement mortar (ISO method)" and GB / T 23445-2009 "Polymer cement waterproof coating". The specific operation is as follows: Take the cured sample (size 50mm×50mm×20mm, mass about 50g), and measure the initial volume (V0) with a vernier caliper, accurate to 0.1mm 3 The sample was immersed in 200 mL of deionized water (25°C constant temperature), sealed and placed in a 25°C constant temperature box, and taken out at 0 h, 24 h, and 48 h of immersion, and the volume (V) was measured by the water displacement method. t ), the drainage method is to place the sample into a graduated cylinder filled with water (accuracy 0.1mL), and the volume of the overflowed water is the sample volume; volume expansion rate (%) = [(V t -V0) / V0]×100%, and take the average value of 3 measurements.
[0080] 2. The water resistance test is based on MT / T 180-2000 "Plastic mesh false roof for underground coal mines" and GB / T 5208-2014 "Flash Dryer". The specific operation is as follows: take the cured sample (mass m0 ≈ 50g), immerse it in 200mL of deionized water (constant temperature of 25℃), seal it and place it in a constant temperature box at 25℃ for 72h; after taking it out, use filter paper to absorb the surface moisture (no visible water droplets), weigh the mass after immersion (m1), with an accuracy of 0.01g; mass retention rate (%) = (m1 / m0) × 100%, and take the average value of 3 measurements.
[0081] 3. Bond strength test: The test was conducted in accordance with GB / T 3903.3-2008, “Adhesives for shoes and bags – Determination of tensile shear strength” and GB / T 23445-2009, “Polymer cement waterproof coatings”. The specific procedure was as follows: 50 g of the cured sample was mixed evenly with 50 g of dry granite particles (particle size 2-5 mm, crushing value ≤15%, in accordance with GB / T 14685-2022, “Pebbles and crushed stone for construction”), poured into a φ50 mm × 50 mm cylindrical mold (with a release agent applied to the inner wall), and cured according to the preparation method in the example (40°C / 2 h + 60°C / 4 h). After demolding, the sample surface was sanded with sandpaper (to remove burrs) to ensure a smooth bonding surface. The sample was stretched at a rate of 0.5 mm / min using a universal material testing machine (accuracy ±0.5% FS, range 0-50 kN), and the maximum pull-out force (F) was recorded. Bond area (S) = π × (25 mm) 2 , bonding strength (MPa) = F / S, take the average value of 3 samples.
[0082] 4. The curing time test is based on GB / T 1728-1989 "Determination of Drying Time of Paint Film and Putty Film" and GB / T2793-1995 "Determination of Non-volatile Matter Content of Adhesives". The specific operation is as follows: take 100g of mixed slurry (according to the proportions in the example), pour it into a φ50mm×10mm shallow dish (with a flat surface), and place it in a constant temperature and humidity chamber at 25°C (humidity 60±5%); the initial setting time is the time when a glass rod touches the surface of the slurry lightly with a finger and no marks are left and the slurry is not sticky; the final setting time is the time when a steel needle is inserted vertically into the slurry and no clear scratches are left on the needle tip after it is pulled out; observe every 5 minutes, record the initial and final setting times, and take the average value of 3 tests.
[0083] 5. Compressive strength test is based on GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete" and GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". The specific operation is as follows: 100g of slurry is injected into a φ50mm×100mm cylindrical mold (with a release agent applied to the inner wall), and cured according to the preparation method in the example (40℃ / 2h+60℃ / 4h); after demolding, the size is measured with a vernier caliper (accuracy 0.1mm), and the cross-sectional area (S=π×(25mm)) is calculated. 2 ); Use a pressure testing machine (accuracy ±1%, range 0-200 kN) to load at a rate of 2 mm / min, and record the maximum load at failure (P); compressive strength (MPa) = P / (S×100), taking the average value of 3 specimens.
[0084] 6. Performance test results:
[0085] Table 1: Performance test results of various embodiments and comparative examples
[0086]
[0087] As can be seen from Table 1, the self-expanding water-blocking material of the present invention significantly solves the performance shortcomings of traditional water-blocking materials in complex tunnel environments, compared with comparative examples 1-3 (no nano-SiO2, no nano-montmorillonite or low filler), through the synergistic effect of modified polyurethane, modified epoxy acrylate, super absorbent resin and nanofiller: its 24h volume expansion rate reaches 278%-292% (compared to 210%-265% for comparative examples 1-3). The higher expansion rate enables it to quickly penetrate and fill the complex geometric space of tunnel cracks, adapting to different sizes and The material has a 72h mass retention rate of 90%-94% (82%-88% for comparison examples 1-3), indicating that the material can maintain structural stability in a long-term immersion environment, effectively solving the problem of late failure of traditional materials due to poor water resistance; the bonding strength with the granite surrounding rock reaches 2.6-3.0MPa (1.9-2.4MPa for comparison examples 1-3), significantly enhancing the interfacial bonding between the material and the surrounding rock, avoiding shedding or sealing failure due to weak bonding; the comprehensive curing time is more reasonable and the construction efficiency is higher. Through multi-component collaborative optimization, the material's high expansion rate, strong water resistance, excellent adhesion and adapted curing time enable it to efficiently fill complex cracks and provide long-term stable sealing, comprehensively overcoming the limitations of traditional water blocking materials such as insufficient expansion rate, poor water resistance, low bonding strength and long curing time.
[0088] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.
Claims
1. A self-expanding water plugging material, characterized in that: In terms of mass percentage, the raw materials include: Modified polyurethane: 30-40%; Modified epoxy acrylate: 25-35%; Super absorbent resin: 10-15%; Filler: 15-20%; Dibutyl phthalate: 1-3%; Ammonium persulfate: 0.5-2%; N,N'-methylenebisacrylamide: 0.5-1%; Silicone defoamer: 1.5-4%; Deionized water: balance; The preparation method of the modified polyurethane comprises the following steps: A1, firstly, dehydrating the polyether diol under vacuum at 110-115°C, cooling the polyether diol to 60-62°C, adding diisocyanate, and heating the polyol to 80-82°C for reaction; then, cooling the polyol to 39-41°C, adding a mixed solution of a carboxyl chain extender and acetone, stirring the mixture, and heating the mixture to 60-63°C for reaction; A2, dispersing nano-SiO2 in anhydrous ethanol and ultrasonically treating the mixture, adding a silane coupling agent and continuing ultrasonication to obtain a dispersion, and dropwise adding the dispersion into the prepolymer for reaction; cooling the polyol to 30-33°C, adding triethylamine, stirring the mixture to form a stable emulsion, and performing reduced pressure distillation.
2. The self-swelling water blocking material according to claim 1, characterized in that: In step A1, the vacuum dehydration time is 2-3 hours; the temperature is raised to 80-82°C and the reaction time is 2-4 hours; the stirring time is 15-20 minutes; The temperature is raised to 60-63°C and the reaction time is 2-4 hours.
3. The self-swelling water blocking material according to claim 1, characterized in that: In step A2, the ultrasonic treatment time is 30-40 minutes; the ultrasonic treatment time is continued for 10-20 minutes; the dispersion is added dropwise to the prepolymer at a rate of 5-6 mL / min, the temperature in the prepolymer is 60-62° C., and the reaction time is 1-2 hours; the stirring speed is 800-850 rpm, and the stirring time is 10-15 minutes.
4. The self-swelling water blocking material according to claim 1, characterized in that: The preparation method of the modified epoxy acrylate comprises: firstly, mixing epoxy resin and methyl methacrylate, heating to 80-82° C., adding a mixed solution of a silane coupling agent and anhydrous ethanol, stirring, adding benzoyl peroxide to initiate polymerization, and heating to 90-92° C. for reaction; B2, subsequently dispersing nano-montmorillonite in deionized water, adding hexadecyltrimethylammonium bromide for ultrasonic dispersion to form an intercalated nano-montmorillonite dispersion, adding the intercalated nano-montmorillonite dispersion to the above-mentioned prepolymer and continuing the reaction; cooling to 60-62° C., adding acrylic acid and a polymerization inhibitor hydroquinone, stirring, heating to 70-72° C. for reaction, and reducing the pressure.
5. The self-swelling water blocking material according to claim 4, characterized in that: In step B1, the mixed solution is stirred for 10-20 minutes, and the temperature is raised to 90-90° C. for a reaction time of 2-3 hours.
6. The self-swelling water blocking material according to claim 4, characterized in that: In step B2, the ultrasonic dispersion time is 2-3 hours; the dropwise addition rate of the nano-montmorillonite dispersion to the prepolymer is 3-4 mL / min, the temperature in the prepolymer is 80-82°C, and the reaction time is continued for 1-2 hours; the stirring time is 10-20 minutes, and the temperature is raised to 70-72°C and the reaction time is 1.5-2 hours.
7. A method for preparing the self-swelling water shutoff material according to any one of claims 1 to 6, characterized in that the steps include: S1. After weighing the raw materials according to the formula ratio, add modified polyurethane and modified epoxy acrylate premix in a high-speed mixer in sequence; Then, super absorbent resin, calcium carbonate, silica powder, dibutyl phthalate, and N,N'-methylenebisacrylamide were added in sequence and stirred; S2. Then, ammonium persulfate and an organosilicon defoamer are added and stirred to obtain a mixed slurry. Finally, the mixed slurry is injected into a mold, placed in a constant temperature box at 40-42° C. for curing, and then heated to 60-65° C. for curing.
8. The preparation method according to claim 6, characterized in that In step S1, the premixing speed is 300-400 rpm, and the premixing time is 5-10 min; the stirring speed is 800-1000 rpm, and the stirring time is 15-20 min.
9. The preparation method according to claim 6, characterized in that In step S2, the stirring time is 5-10 minutes; the curing time in a 40-42°C constant temperature box is 2-4 hours, and the curing time at 60-65°C is 4-6 hours.
10. Use of the self-swelling water-blocking material according to any one of claims 1 to 6 or the self-swelling water-blocking material prepared by the preparation method according to any one of claims 7 to 9, characterized in that: Application of the self-expanding water blocking material in tunnels.
Citation Information
Cited By
Quick-curing polyurethane seamless expansion joint material for roads and preparation method thereof
CN121022087A